Synthesis, Structure, Luminescence and Thermal Stable Properties of Zn(II) Coordination Polymer Constructed from 2-Hydroxyphenylacetic Acid and 4,4’-Trimethylenendipyridine - Hao, Xiao-Min; Chen, Gang; Gu, Chang-Sheng (Asian Journal of Chemistry, 2014)
A novel complex 1 of [Zn(tdp)(dpa)2]n (Hdpa: 2-hydroxyphenylacetic acid; tdp: 4,4'-trimethylenendipyridine) was prepared and characterized by elemental analysis, IR, TGA, X-rey single crystal diffraction. The carboxylate oxygens of the 2-hydroxyphenylacetic acid (Hdpa) ligands connect one Zn(II) ion in monodentate coordinated modes to form mononuclear zinc(II) building blocks, which are further linked into a 1D infinite chain through trans-tdp igands. Furthermore, the luminescent properties of 1 was also investigated.